The tycoon's diamond demand - Wood, Joss (Harlequin presents. Larger print, 2024)
Self-made CEO Jens Nilson has spent the past decade trying to even the score against the woman who jilted him and her father, who almost destroyed him. The best way to do that? Demand Maja Hagen marry him--and leave her at the altar. After Maja fled their elopement, she built herself a new life away from her father's tyranny. She won't let Jens jeopardize that, even if it means accepting his proposal! But their rekindled desire is already threatening to incinerate her every defense against him...